Pengaruh Manual Mobilisasi Saraf Terhadap Penurunan Nyeri Pada Pasien Ischialgia Pasca Terapi IR Dan TENS Di RSD KRMT Wongsonegoro Semarang - Widya Ervianta; Lilik Sigit Wibisono; Rafif Aydin Maheswara; Aisya Rahmah (Asosiasi Riset Ilmu Kesehatan Indonesia, 2023)
Low back pain (NPB) Ischialgia is the pinching of the ischiadic nerve in the lower back region which causes the buttocks, thighs, lower legs and even feet to tingle, pain, sometimes causing weakness. Nerve mobilization is a manipulation technique by moving and stretching the nerve tissue to improve axonal transport so as to improve nerve conduction. Nerve mobilization can reduce the pressure in the nerve so that there is an increase in blood flow to the nerve, which can have a regenerating and healing effect on the injured nerve (Butler, 1991). Nerve mobilization is often used as a form of diagnosis and treatment in musculoskeletal conditions with nerve involvement (Butler, 1991). Nerve mobilization in the Lower Limb Tension Test (LLTT) is performed on the branching of the lumbosacral plexus such as the ishiadicus nerve, peroneal nerve, and tibial nerve. But here the author only discusses LLTT on the ishiadicus nerve, namely LLTT 1 which is associated with low back pain. The purpose of knowing the effect of manual nerve mobilization on pain reduction in Ischialgia patients after IR and TENS therapy at RSD KRMT Wongsonegoro Semarang. Method two group pre test and post test. The place of this research is in the physiotherapy clinic of KRMT Wongsonegoro Hospital. Using Visual Analouge Scale (VAS) measuring instrument. The results were treated using the mann-Whtney test. With confidence interval (CI) (95%) The results revealed that there was a significant difference in pain between group 1 (p = 0.00) and group 2 (p = 0.00). But there was no significant difference between the two groups on pain improvement (p = 0.152), so there was no better treatment between the two groups. It is concluded that ULTT is useful in the treatment of LBP patients to reduce pain in two groups. The targeted output is publication in Sinta indexed national journals and IPR. The TKT target of the implementation of gamelan accompaniment gymnastics is at level 2.